(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The increase in vehicles with automatic transmission has a significant impact on the dynamics of urban transport. This article examines the impact of automatic transmission vehicles on traffic flow rates on city streets, focusing on their advantages and potential problems . Through a combination of theoretical calculations, simulations, and empiric experiments, the impact of these vehicles on traffic flow rates and congestion levels was evaluated . Research aims to inform urban planning and transport management strategies.